Analysing inverse heat conduction problems by the analysis of the system impulse response - Löhle, S; Fuchs, U; Digel, P; Hermann, T; Battaglia, J-L (Taylor and Francis, 2013)
The paper presents the application of the non-integer system identification (NISI) method with a focus on the analysis of the system’s impulse response. The NISI method being first published in 2001 has been applied to very different inverse heat conduction problems. The results presented in this paper are new findings developed by considering the impulse response as the characteristic of the investigated system. This assumption allows a different view to the problems where the method so far has been restricted. Examples are shown for a system with variable thermophyiscal properties and a surface under transpiration cooling.